Effort, Revenue, and Cost Sharing Mechanisms for Collaborative New Product Development - Bhaskaran, Sreekumar R.; Krishnan, V. (Management Science, 2009)
The growing sophistication of component technologies and the rising costs and uncertainties of developing and launching new products require firms to collaborate in the development of new products. However, the management of new product development that occurs jointly between firms presents a new set of challenges in sharing the costs and benefits of innovation. Although collaboration enables each firm to focus on what it does best, it also introduces new issues associated with the alignment of decisions and incentives that have to be managed alongside conventional performance and timing uncertainties of new product development. In this paper, we conceptualize and formulate the joint development of products involving two firms with differing development capabilities and examine the implications of arrangements that go beyond sharing of revenues to include sharing of development cost and work. We term these approaches that involve sharing of the development cost and sharing of the development work investment sharing and innovation sharing, respectively. These cost and effort sharing mechanisms have subtle interactions with the degree to which revenues are shared between firms and the type of development project under consideration. Our analysis shows that investment and innovation sharing are particularly relevant for products with no preexisting revenues, and their benefits also depend on the degree to which revenues are shared between the firms. Whereas investment sharing is more attractive for new-to-the-world product projects with significant timing uncertainty, innovation sharing plays an important role in environments where projects experience product quality uncertainty, firms are similar in their capabilities, and the costs of integration of work across firms can be controlled. Our key contribution involves the modeling of joint work and decision making between collaborating firms and unearthing the complementary role of revenue, cost, and innovative effort sharing mechanisms for new product development. We translate our analytical findings into a managerial framework and illustrate the results with examples from the life-sciences and electronics industries.